"Surplus Woman": Female Sexuality and the Concept of Endogamy. Issue 1 (February 2021) - Mitra, Durba
Abstract : This essay traces the colonial origins of the concept of endogamy and its history as a foundational idea in the modern study of society in South Asia. The history of the concept of endogamy reveals how the control of female sexuality shaped the overlapping fields of Indology and ethnology. The invention and deployment of endogamy in the nineteenth and early twentieth centuries is discussed in the writings of key colonial writers and British administrators, such as J. F. McLennan and H. H. Risley, and Indian intellectuals, including S. V. Ketkar and B. R. Ambedkar. It argues that the modern study of caste naturalized the control of female sexuality through the uncritical use of the concept of endogamy, which Ambedkar diagnosed as the irresolvable problem of the "Surplus Woman" in 1917. The essay reflects on the long life of endogamy and the enduring problem of nonconjugal sexuality in modern social theories of South Asia.